(untitled) (Global Journal of Science Frontier Research, 2021)
Water and sediment samples were collected from Onyima Creek (Ede Onyima) for eight months at intervals of two months to analyze the level of distribution and possible sources of total petroleum hydrocarbons contamination. Petroleum hydrocarbons components were determined by Gas Chromatography-Flame Ionization Detector (GC-FID) and then quantified after necessary extraction procedures and, laboratory pretreatment have been performed. The petroleum hydrocarbons chain length recorded ranged from C 8 -C 40 in both water and sediment columns. The total petroleum hydrocarbons recorded in the water column of the creek ranged from 10.485-24.762mg/L, while in the sediments, recorded value ranged from25.460-69.357mg/Kg. The source identification ratios and indices used include C 31 /C 19 , CPI, ACL, C 15 -C 19 odd hydrocarbons, C 18 -C 22 even hydrocarbons, LHC/SHC, and, L/H showed that the origin of total petroleum hydrocarbons contamination in the creek was from natural and anthropogenic sources. There is, therefore, the need for control and regulation of activities that contributed to the presence of total petroleum hydrocarbons in the creek to safeguard human health and aquatic plants and animals that dwell in the Onyima Creek (Ede Onyima) space.